Mulheres no mundo da aviação: quem são elas? - Bertulucci, Sandra Fabiola Estigarribia Salinas (2019)
A woman from the aviation world, ever since the beginning, I was present in a field of action seen as strictly masculine. Today, the quantities of ladies are growing in this world though restricted but never prohibited. The social standards the women in this field came to see as an obstacle to the family and society, but these days, they are seen as examples of glamour and courage. Those who like to live in the air. Early in the twentieth century, Alberto Santos Dumont, a brave and visionary man, presented an aircraft heavier than air that should be sustained by aerodynamic reactions. On a bike, he shouted instructions to the woman training in the aircraft, a man who believed that both men and women could have been born with the bird's heart. We start from the assumption that, although the field of aviation has always been and still is resistant to the entry of women as pilots or aircraft commanders, the stereotype has been gradually broken by the female gender, which escapes professional functions defined socially and culturally, as the most suitable for women. The thesis advocated here is equality of women in the aviation world, because women want and can fly. The objective of this study is to give visibility to the women who decided to work in the field of Aviation, seeking, in this way, a professional career. A bold attitude on the part of certain women that leads us to ask: What motivates them to seek this profession of masculine dominance? What are the difficulties encountered in entering or being accepted in this field? What are the difficulties experienced in the exercise of the profession due to the female condition? In Material and Method, we set out to conduct a qualitative research, based on open interviews. Results obtained: The profile of women who perform the role of pilots is explicit